“Comparison of Octreotide and Terlipressin Efficacy in Prevention of Early Variceal Rebleed after Endoscopic Variceal Band Ligation’’ (Journal of Fatima Jinnah Medical University, 2018)
Objectives: Terlipressin and octreotide are both used as adjuvant therapy to endoscopic variceal band ligation however data is scarce on the head-to-head efficacy of terlipressin and octreotide in prevention of early variceal rebleed. The aim of this study was to compare the efficacy of terlipressin with octreotide as an adjuvant therapy to endoscopic variceal band ligation in patients with esophageal variceal bleeding.Methods: This study (a comparative interventional study) was conducted in Medical Unit II, Jinnah hospital Lahore from December 2012 to June 2013 and 150 patients were included in this study. Cirrhotic patients with esophageal variceal bleed were randomized on admission to receive octreotide (group A) or terlipressin (group B) after endoscopic variceal band ligation. The two groups were compared for prevention of early variceal rebleed.”Control of variceal bleed” was the measure of efficacy of terlipressin and octreotide.Results: One hundred and fifty patients were included in the study. Re-bleeding occurred in 16 patients (21.33 %) in study group A and in 12 patients (16 %) in study group B (p= 0.402).Conclusion: It is concluded that terlipressin is as effective in prevention of early variceal rebleed after endoscopic band ligation as octreotide, with minor superiority. Therefore both drugs can be used for prevention of early variceal rebleed after band ligation.